Migrating Birds Optimization: A New Meta-heuristic Approach and Its Application to the Quadratic Assignment Problem - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2011)
In this study we propose a new nature inspired metaheuristic approach based on the V formation flight of the migrating birds which is proven to be an effective formation in energy minimization. Its performance is tested on quadratic assignment problem instances arising from a real life problem and very good results are obtained. The quality of the solutions turned out to be better than simulated annealing, tabu search and guided evolutionary simulated annealing approaches. These results indicate that our new metaheuristic approach could be an important player in metaheuristic based optimization.
Keywords: metaheuristics; simulated annealing; optimization; FORMATION FLIGHT; ENERGY SAVINGS; ALGORITHM; SEARCH